Labeling viral envelope lipids with quantum dots by harnessing the biotinylated lipid-self-inserted cellular membrane. (November 2016) - Lv, Cheng; Lin, Yi; Liu, An-An; Hong, Zheng-Yuan; Wen, Li; Zhang, Zhenfeng; Zhang, Zhi-Ling; Wang, Hanzhong; Pang, Dai-Wen
Abstract: Highly efficient labeling of viruses with quantum dots (QDs) is the prerequisite for the long-term tracking of virus invasion at the single virus level to reveal mechanisms of virus infection. As one of the structural components of viruses, viral envelope lipids are hard to be labeled with QDs due to the lack of efficient methods to modify viral envelope lipids. Moreover, it is still a challenge to maintain the intactness and infectivity of labeled viruses. Herein, a mild method has been developed to label viral envelope lipids with QDs by harnessing the biotinylated lipid-self-inserted cellular membrane. Biotinylated lipids can spontaneously insert in cellular membranes of host cells during culture and then be naturally assembled on progeny Pseudorabies virus (PrV) via propagation. The biotinylated PrV can be labeled with streptavidin-conjugated QDs, with a labeling efficiency of ∼90%. Such a strategy to label lipids with QDs can retain the intactness and infectivity of labeled viruses to the largest extent, facilitating the study of mechanisms of virus infection at the single virus level.